Comparison between standard and non-standard finite difference methods for solving first and second order ordinary differential equations - Yaghoubi, Abdulrahman; Saberi Najafi, Hashem (International Journal of Applied Mathematical Research, 2015)
In this paper, we solve some first and second order ordinary differential equations by the standard and non-standard finite difference methods and compare results of these methods. Illustrative examples have been provided, and the results of two methods compared with the exact solutions.